2005
DOI: 10.1038/nature03610
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transfer in the arbuscular mycorrhizal symbiosis

Abstract: Most land plants are symbiotic with arbuscular mycorrhizal fungi (AMF), which take up mineral nutrients from the soil and exchange them with plants for photosynthetically fixed carbon. This exchange is a significant factor in global nutrient cycles as well as in the ecology, evolution and physiology of plants. Despite its importance as a nutrient, very little is known about how AMF take up nitrogen and transfer it to their host plants. Here we report the results of stable isotope labelling experiments showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
638
5
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 881 publications
(679 citation statements)
references
References 28 publications
31
638
5
5
Order By: Relevance
“…Several studies revealed that approximately 20 to 75% of the total N uptake of AM plants can be transferred by AMF to their hosts (Govindarajulu et al 2005;Tanaka and Yano 2005). An observed wide range of mycorrhizal growth responses of rice plants in response to nutrient availability, however, impedes understanding of the molecular mechanisms underlying this N transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed that approximately 20 to 75% of the total N uptake of AM plants can be transferred by AMF to their hosts (Govindarajulu et al 2005;Tanaka and Yano 2005). An observed wide range of mycorrhizal growth responses of rice plants in response to nutrient availability, however, impedes understanding of the molecular mechanisms underlying this N transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Govindarajulu et al 2005;Koegel et al 2013a,b; reviewed by Courty et al 2015). Due to high energy costs of NO 3 − to NH 4 + reduction, microorganisms normally prefer the direct assimilation of NH 4 + (Courty et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…GzRPS16 has been annotated as a mitochondrial ribosomal protein S16 that characterized as a human housekeeping gene (Eisenberg and Levanon, 2003). In addition, ribosomal protein S4 has been used as a reference gene for qRT-PCR in a mycorrhizal fungus (Govindarajulu et al, 2005). RPS3 and RPS18 were the most stable in a fungus-infected red flour beetle (Lord et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, legumes can be inoculated with selected symbionts to improve survival in reforestation programs [3,33]. Since Fabaceae can support rhizobia and both EM and AM, the latter being the most frequent [70], plant performance could be favored by nitrogen (N) uptake, either by direct uptake by AM [71] or by the multiple benefits from AM [72].…”
Section: Plants For Reforestationmentioning
confidence: 99%